2011
DOI: 10.4084/mjhid.2011.010
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Hepatitis B Treated with Entecavir

Abstract: Hepatitis B virus (HBV) infection constitutes a serious global health problem. Nowadays there are divergent data regarding the use of antiviral drugs to treat acute hepatitis B. We present here a case of a 62-year-old man affected by severe acute hepatitis B with progressive worsening of clinical and hepatic function. The patient was treated with entecavir without critical side effects. We observed rapid clinical and laboratory improvements and the disappearance of hepatitis B surface antigen (HBsAg). The trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…In the light of our clinical experience and comparing our case series with the positive reports on the use of entecavir in field literature, [13][14][15] for the time being we can consider entecavir to be an option in selected cases with SAHB. It is, however, not possible to determine a recommended duration of treatment based on the scarce data available so far.…”
Section: Discussionmentioning
confidence: 76%
“…In the light of our clinical experience and comparing our case series with the positive reports on the use of entecavir in field literature, [13][14][15] for the time being we can consider entecavir to be an option in selected cases with SAHB. It is, however, not possible to determine a recommended duration of treatment based on the scarce data available so far.…”
Section: Discussionmentioning
confidence: 76%
“…Tillman et al reported that lamivudine is safe in patients with severe acute or fulminant hepatitis B, leading to fast recovery with the potential to prevent liver failure and liver transplantation when administered early enough 313. There have been only a few case reports of antiviral agents as treatment for acute hepatitis B other than lamivudine so far 314-316…”
Section: Treatment Of Special Populationsmentioning
confidence: 99%
“…The few reported cases to date that have used adefovir or entacavir include primary monotherapy use of entacavir in a case series of six German patients20 and two Italian patients,21,22 and rescue therapy with adefovir and entacavir in the two German cases mentioned above 5. All these cases had favorable outcomes.…”
Section: Discussionmentioning
confidence: 98%